Designing production management systems of oil-and-gas holding companies; Korus 2004; Vol. 1 - Kovin R. V. Roman Vladimirovich; Kopnov M. V. Maksim Valerievich; Kudinov A. V. Anton Viktorovich; Markov N. G. Nikolai Grigorevich; Miroshnichenko E. A. Evgeny Alexandrovich; Ostrast P. M.; Sherstnyov V. S.; Shestakov N. A. (2004, 2004)
We consider both principles of designing production management systems of oil-and-gas holding companies and their application while developing the corporative geoinformation system of 'VostokGazProm' holding company.